(4a-3)(a+2)=

Simple and best practice solution for (4a-3)(a+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4a-3)(a+2)= equation:


Simplifying
(4a + -3)(a + 2) = 0

Reorder the terms:
(-3 + 4a)(a + 2) = 0

Reorder the terms:
(-3 + 4a)(2 + a) = 0

Multiply (-3 + 4a) * (2 + a)
(-3(2 + a) + 4a * (2 + a)) = 0
((2 * -3 + a * -3) + 4a * (2 + a)) = 0
((-6 + -3a) + 4a * (2 + a)) = 0
(-6 + -3a + (2 * 4a + a * 4a)) = 0
(-6 + -3a + (8a + 4a2)) = 0

Combine like terms: -3a + 8a = 5a
(-6 + 5a + 4a2) = 0

Solving
-6 + 5a + 4a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-2 + -1a)(3 + -4a) = 0

Subproblem 1

Set the factor '(-2 + -1a)' equal to zero and attempt to solve: Simplifying -2 + -1a = 0 Solving -2 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1a = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1a = 0 + 2 -1a = 0 + 2 Combine like terms: 0 + 2 = 2 -1a = 2 Divide each side by '-1'. a = -2 Simplifying a = -2

Subproblem 2

Set the factor '(3 + -4a)' equal to zero and attempt to solve: Simplifying 3 + -4a = 0 Solving 3 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4a = 0 + -3 -4a = 0 + -3 Combine like terms: 0 + -3 = -3 -4a = -3 Divide each side by '-4'. a = 0.75 Simplifying a = 0.75

Solution

a = {-2, 0.75}

See similar equations:

| 2(x+1)+5=6x-4(-2+x) | | 0.14(y-1)+0.10y=0.08y-0.01(30) | | 6mn^2(5m^3n+4mn^2-2m^2n+mn)= | | x^2+8=33 | | 0.18(y-7)+0.10y=0.04y-0.07(30) | | -80x^5-8x^4= | | -80x^4-8x^4= | | -4.27m^2(2.83m^4+6.82m^2-3.25m^3+2.47)= | | 5y-4+y+31=5y+30-2y | | 80x^5-8x^4= | | 0.60x+.05(20-x)=.10(-1) | | 6x^2-x+1=0 | | -16+x=x+13 | | 25x^3-20x^2+5x=0 | | am^2+16m+1=0 | | b^2(b^2+8)= | | 6x+13x=76 | | 3x^3y+6x^2y^2-12x^2y=0 | | 6(3x+1)=2x-7x | | 12-4x=2x-2 | | 2.03x(1.27x-2.36)= | | -15x^5-5x^4=0 | | 9(3x+1)=4x-7x | | -x+7=28 | | 3(-2-x)= | | x(b+2)= | | 8r+9=-5.37-6 | | 1.8r+9=5.7-6 | | 9v^2+21v+18=0 | | 10b^2-23bc-5c^2= | | 9s^3+15s^2-36s= | | -2(n-7)-(9+6n)=-9n |

Equations solver categories